Prevention and Counteraction to Bullying in Ukraine as a Negative Social Phenomenon - Sokurenko, Valerii; Kharkiv National University of Internal Affairs (2022)
Every State of law that really wants to achieve it's objective in maintaining a stable and democratic society must be able in dealing with those deviant character constituting a threat to the smooth functioning of the society. It is therefore the responsibility of every State of law in ensuring that all conduct of it's citizens must be able in respecting available legal prescription. The State of Ukraine has put in place credible penal laws by combating all acts considered to be bullying and a threat to social life. It is in this regard that a need for this paper was considered necessary, as it articulates the ills or aftermath of failure to effectively combat acts of bullying in Ukraine. In answering the above objective, there was the need to analyses the role of the Ukrainian Penal Laws in matters relating to bullying. From the position of the Criminal Law in Ukraine, one can ascertain that act of bullying continues to be a great pandemic to the society as we continue to experience an increase of this character irrespective of the efforts put in place by the laws. In is therefore in this regards that we think that it is not just providing the punishment of acts of bullying in the laws that is relevant, but in essence ensuring effective and severe punishment to all those considered as perpetrators of the crime concerned.